2015
DOI: 10.1002/j.0022-0337.2015.79.11.tb06028.x
|View full text |Cite
|
Sign up to set email alerts
|

Agreement Among Dental Students, Peer Assessors, and Tutor in Assessing Students’ Competence in Preclinical Skills

Abstract: The aim of this study was to determine the level of agreement regarding assessments of competence among dental students, their student peers, and their clinical skills tutors in a preclinical skills program. In 2012-13 at the University of Edinburgh, second-year dental students learned to perform the following seven cavity preparations/restorations on primary and permanent Frasaco teeth: single-surface adhesive occlusal cavity; single-surface adhesive interproximal cavity; single-surface adhesive labial cavity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 23 publications
3
13
2
Order By: Relevance
“…Our results revealed disagreement between student self‐assessments and faculty member assessments; students tended to underestimate their performance. Other studies have also found disagreement between student self‐assessments and faculty assessments . However, unlike our findings, previous research has found that poorly performing students tend to overrate their performance, while high‐performing students are more self‐critical and tend to underrate it .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results revealed disagreement between student self‐assessments and faculty member assessments; students tended to underestimate their performance. Other studies have also found disagreement between student self‐assessments and faculty assessments . However, unlike our findings, previous research has found that poorly performing students tend to overrate their performance, while high‐performing students are more self‐critical and tend to underrate it .…”
Section: Discussioncontrasting
confidence: 99%
“…However, unlike our findings, previous research has found that poorly performing students tend to overrate their performance, while high‐performing students are more self‐critical and tend to underrate it . Other studies have found that students are more likely to overestimate their competence than their tutors . However, prior investigations did not clarify the effect of self‐assessments on student performance.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies have also shown that gender and personality/psychological characteristics play a role in self‐assessment ability 2 , 4 , 5 , 11 , 13 , 20 . Peer assessments have been found to be typically inflated as well and may not correlate strongly with faculty assessments 4 , 15 , 17 , 18 , 21 . The methodology of many studies has been criticized, particularly by Ward et al and Eva and Regehr, including the lack of validity for faculty interrater reliability to be used as a gold standard for comparison, the limitations of group‐level analysis, and the differential use of scale among students 5 , 11 .…”
mentioning
confidence: 99%
“…One of the patterns in the data collected which was consistent with the ndings of previous studies was the agreement between tutor-assessment and peer-assessment. 15,19 It has been said that under-performing students are more likely to over-estimate their performance and competent students are able to accurately assess their performance. 7 Therefore, these students who assessed their performance accurately (70% of the time) and when not in agreement with their tutor, under-estimated themselves are likely to be competent in their eld.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that students needed more training to enhance both their self-and peer-assessment skills, as there was poor correlation between the three assessment types, with students over-estimating their own, as well as their peers, performance in comparison to the tutor's evaluation. 19 This outcome would suggest that students need more training in assessment, or that they do not hold the level of expertise required to measure and evaluate to a satisfactory level.…”
Section: Introductionmentioning
confidence: 99%